Hot Rolled Ti6321 Alloy Sheets With Different Initial Microstructures: Microstructure, Mechanical Properties, and Anisotropy Characteristics - Fan, Jiangkun; Huang, Hao; Xue, Xiangyi; Zhang, Wenyuan; Wang, Yang; Zhang, Binbin; Tang, Bin; Zhao, Ruifeng; Kou, Hongchao; Li, Jinshan (Frontiers in Materials, 2020)
The microstructure, mechanical properties and texture characteristics of marine titanium alloy Ti6321 sheets with four different initial microstructures were investigated contrastively in this paper. The results indicate that the strength of hot-rolled, equiaxed and bimodal microstructure sheets exhibits significant anisotropy in the RD and TD directions. The hot rolled sheet shows the strongest anisotropy of tensile properties, that is, the transverse yield strength is 91 MPa higher than that of the rolling direction. And the morphology characteristics of the macroscopic tensile fracture are also significantly different in RD and TD. The strength anisotropy of Ti6321 alloy sheet decreases with the increase of annealing temperature. The mechanical properties of the widmanstätten microstructure sheet are close to isotropic and the plasticity is the worst among the four initial microstructures. The root cause for the properties anisotropy was analyzed by XRD and EBSD. There is a strong (1 ̅21 ̅0)[101 ̅0] prismatic texture and a relatively weak (1 ̅21 ̅0)[0001] basal texture in the anisotropic sheet. The anisotropic characteristics of the tensile deformation of Ti6321 alloy sheet at room temperature are mainly attributed to the difference in the Schmid factor of basal slip system and prismatic slip system in TD and RD specimens.